Factors influencing chopstick use and an objective identification of traditional holding techniques in children. - Yuki Choji; Nanami Hirokawa; Chie Morimoto; Norihito China; Akio Nakai; Kazunori Miyata (PLoS ONE)
The acquisition of chopstick skills is considered essential for child development and etiquette in many Asian cultures. However, a decline in chopstick education has been observed in Japan, and the underlying causes of this phenomenon remain elusive. This study aims to investigate children's chopstick skills and develop an objective method to evaluate them using a hand posture estimation model. In this study. A questionnaire survey was conducted among 165 first-grade elementary school students (aged 6-7) and their parents to investigate factors influencing chopstick proficiency. To complement this, video analyses were performed using a hand posture estimation model to assess the accuracy of chopstick grip classification. The findings showed that children's chopstick-holding styles could be classified into four categories: four-finger prehension (64 participants), three-finger prehension (49 participants), palm prehension (20 participants), and others (32 participants). Despite the fact that over 80% of parents reported teaching their children how to use chopsticks, a mere 9.7% of children exhibited correct chopstick-holding technique. Interestingly, factors such as intergenerational cohabitation with grandparents and child's age significantly influenced chopstick proficiency. These results indicate that a gap exists in the intergenerational transmission of chopstick skills, with parents potentially lacking sufficient knowledge to teach their children. The hand posture estimation model had a high accuracy rate of 85%, precision of 83%, and recall of 88% to identify whether children use chopsticks traditionally. While chopstick education is predominantly conducted within Japanese households, the increasing prevalence of nuclear families and dual-income households suggests a decline in intergenerational transmission of chopstick education. To address this issue, it is imperative to develop web applications that can integrate chopstick education into school curricula and promote chopstick skills among students.